2023
DOI: 10.1002/aelm.202300195
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Physically Unclonable Functions Based on Nanoscale Voltage‐Controlled Magnetic Tunnel Junctions

Abstract: With the fast growth of the number of electronic devices on the internet of things (IoT), hardware-based security primitives such as physically unclonable functions (PUFs) have emerged to overcome the shortcomings of conventional software-based cryptographic technology. Existing PUFs exploit manufacturing process variations in a semiconductor foundry technology. This results in a static challenge-response behavior, which can present a long-term security risk. This study shows a reconfigurable PUF based on nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Typically, it involves an MTJ device characterized by a high resistance-area (RA) product. [69][70][71] As a result, the current that passes through the thin insulating barrier is extremely minimal, enhancing the energy efficiency of VCMA and making it appealing for a wide range of applications, such as MRAMs, 72,73 random number (RN) generators, [74][75][76] physically unclonable functions (PUFs), [77][78][79] neuromorphic computing, 80,81 and spintronic oscillators. [82][83][84][85][86][87] In this article, our primary focus is the VCMA-MRAM, which is discussed in Secs.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, it involves an MTJ device characterized by a high resistance-area (RA) product. [69][70][71] As a result, the current that passes through the thin insulating barrier is extremely minimal, enhancing the energy efficiency of VCMA and making it appealing for a wide range of applications, such as MRAMs, 72,73 random number (RN) generators, [74][75][76] physically unclonable functions (PUFs), [77][78][79] neuromorphic computing, 80,81 and spintronic oscillators. [82][83][84][85][86][87] In this article, our primary focus is the VCMA-MRAM, which is discussed in Secs.…”
Section: Introductionmentioning
confidence: 99%
“…Spintronic PUFs are being developed as an alternative to tackle these challenges and enable the development of on-chip PUFs integrated with CMOS technology. A recent study demonstrated the secure access and data protection capabilities of CMOS-integrated on-chip spintronic PUFs within in-memory computing . However, despite advances in spintronic or MRAM-based PUFs, some of the crucial PUF properties remain to be verified for practical applications.…”
mentioning
confidence: 99%